Spectrophotometric Determination of Isoniazid from Pharmaceutical Preparations Using Natural Aldehyde - Almani, K.F.; Laghari, M.G.H.; Memon, A.H.; Rind, F.M.A.; Mughal, U.R.; Maheshwari, M.L.; Khuhawer, M.Y. (Asian Journal of Chemistry, 2012)
A spectrophotometric method has been developed for the micro determination of isoniazid from various pharmaceutical dosage forms. Method is based on a condensation reaction between isoniazid and ethanolic solution of cis-cinnamaldehyde to generate an instant yellow coloured schiff's base derivative of isoniazid. The coloured product formed absorbed in visible region and optimal detector response was obtained at a wavelength of 364 nm with a molar absorptivity of 3.1 × 104 L/mol/cm. The analytical parameters and their effects on the reported systems are investigated. A linear relationship was obtained between the absorbance and the concentration of the derivative which obeyed the Beer's law within 0.5-2.5 μg/mL. The low % relative standard deviation (0.2-1.5) values indicate good precision, high recovery values and accuracy of proposed method.